The Constitutional Thought of Pedro Planas - Cairo Roldán, Omar (2008)
This paper develops the elements of the constitutional thought of Pedro Planas. In that sense it establishes the concept of Constitutional Democracy, analyzes its characteristics, such as the division of powers and the supremacy of the Constitution, and develops its differences with respect to the autocracy, which according to this, is the political system. Following this same line, the basic structures of the political regimes in the Constitutional Democracy are analyzed. This is developed in two parts, in the first, the political schemes are divided according to the system of checks and balances, from this the existence of two types of regimes is concluded: the parliamentary regime and the presidential regime. In the second part, the regimes are distinguished according to the origin of the governmental power structure, in this sense, two options are established: i) of basically parliamentary structure and ii) of basically presidential structure. It is important to mention that Pedro Planas states that during the analysis of these forms it is normal to find mixtures, which are understood as a third system (tertium). Likewise, the author develops the types of State that can exist according to the territorial organization of political power in the constitutional Democracy. There are three main types: i) Unitary state, ii) Federal state and iii) Confederation. On the other hand, the author analyzes the position of Pedro Planas regarding the structure of polite regimes in Latin America; concluding that the predominant political regime in Latin America is presidentialism and that it follows the model of European regimes. Subsequently, the concept of Social State of Law is analyzed, establishing that this arises from the confluence between the Rule of Law and the Social State. The author develops the position of Pedro Planas regarding the distinction between the History of the Constitutions and the Constitutional History. As last points, we analyze the form of government and decentralization in Peru.